ANALISIS DAN PERANCANGAN PRIVATE CLOUD STORAGE MENGGUNAKAN METODE IDS(INTRUSION DETECTION SYSTEM) DAN IPS(INTRUSION PREVENTION SYSTEM) STUDI KASUS DINAS KOMUNIKASI DAN INFORMATIKA KOTA PADANG PANJANG - Meiditra, Irzon; Yuhandri; Sumijan (Fakultas Ilmu Komputer, Universitas Pasir Pengaraian, 2023)
The Office of Communication and Informatics of the City of Padang Panjang is an executive element of government affairs in the field of communication, informatics, coding and statistics and has the task of carrying out government affairs in the field of communication and informatics. And the Communication and Informatics Office has a server storage service with lots of data. The development of a cloud computing server will be a solution. Cloud computing is a form of technological progress that has developed along with the times, this has spurred the increasing use of the internet. Using internet technology that is capable of implementing virtual/online servers, which has the goal of building a cloud computing server at the Padang Panjang City Communication and Information Service Operating System (OS) Proxmox VE (Virtual Environment). Cloud computing is a form of technological progress that has developed along with progress of the times, this spurred the use of the internet which is increasing. By using internet technology that is capable of implementing virtual/online servers, the aim is to build a cloud computing server at the Padang Panjang City Communication and Information Service Operating System (OS) Proxmox VE (Virtual Environment) 6.4. Cloud computing is able to provide storage services that can be used simultaneously. The results of this study produce a cloud Storage server that implements a security system using the ids (intrusion detection system) and ips (intrusion prevention system) methods that is capable of carrying out data storage processes (storage), using software simultaneously in the network, and using infrastructure within the scope of cloud computing network at the Padang Panjang City Communication and Information Service using the private cloud Storage service model.